2006
DOI: 10.1079/bjn20061752
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolaemic effects of milk-kefir and soyamilk-kefir in cholesterol-fed hamsters

Abstract: This study aimed to evaluate the hypocholesterolaemic property of milk-kefir and soyamilk-kefir. Male hamsters were fed on a cholesterol-free or cholesterol-enriched diet containing 10 % skimmed milk, milk-kefir, soyamilk or soyamilk-kefir for a period of 8 weeks. The soyamilk, milk-kefir and soyamilk-kefir diets all tended towards a lowering of serum triacylglycerol and total cholesterol concentrations, and a reduction of cholesterol accumulation in the liver, the decrease in serum cholesterol concentration b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 40 publications
2
70
0
7
Order By: Relevance
“…The lower values of total cholesterol in the groups that received kefir show that kefir beverages are probiotic and have hypocholesterolemic effects [24] as demonstrated in other studies with milk kefir and water kefir [25,26].…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 53%
“…The lower values of total cholesterol in the groups that received kefir show that kefir beverages are probiotic and have hypocholesterolemic effects [24] as demonstrated in other studies with milk kefir and water kefir [25,26].…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 53%
“…While it has been widely consumed in Russia and central Asia contries such as Kazakhstan, Kyrgyzstan for centuries, it is now increasingly popular in European countries, Japan and the United States due to its nutritional and therapeutic effects (Otles & Cagindi, 2003). Previous studies on kefir have reported antimicrobial, immunological, anti-tumour and hypocholesterolaemic effects, as well as β-galactosidase activity (de Moreno de LeBlanc, Matar, Farnworth, & Perdigon, 2006;Garrote, Abraham, & De Antoni, 2000;Hertzler & Clancy, 2003;Liu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the beverage contains a mixture of lactic acid, carbon dioxide, acetaldehyde, ethanol and vitamin B12 3 . Its consumption has been associated with the improvement of the immune system, antitumor activity and reduction of cholesterol 4,5 .…”
mentioning
confidence: 99%